2020
DOI: 10.1186/s12936-020-03350-1
|View full text |Cite
|
Sign up to set email alerts
|

Stocking pattern for anti-malarial medications among proprietary patent medicine vendors in Akinyele Local Government Area, Ibadan, Nigeria

Abstract: Background: Policymakers have recognized that proprietary patent medicine vendors (PPMVs) can provide an opportunity for effective scaling up of artemisinin-based combination therapy (ACT) since they constitute a major source of malaria treatment in Nigeria. This study was designed to determine the stocking pattern for anti-malarial medications, knowledge of the recommended anti-malarial medicine among PPMVs in Akinyele Local Government Area (LGA) of Oyo State, Nigeria and their perception on ways to improve P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Additionally, Akinyele LGA comprises 12 wards, consisting of both rustic and developed localities, with a significant portion of the residents depending on farming as a means of livelihood. 18,19 Study design and population. The study design was cross sectional.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, Akinyele LGA comprises 12 wards, consisting of both rustic and developed localities, with a significant portion of the residents depending on farming as a means of livelihood. 18,19 Study design and population. The study design was cross sectional.…”
Section: Introductionmentioning
confidence: 99%
“…28 Self-medication practice observed in the population is attributed to inexpensive drugs, the level of trust of self-medication evidenced by positive reports from friends and family members, readily available drugs for purchase over the counter without a professional prescription note, education status, and the financial cost of hospitals, which are similar to reports from different geographical locations. 12,26,29,30 Our study revealed that the majority of caregivers could not correctly differentiate between symptoms of malaria and other diseases and that they could not correctly select drugs for malaria treatment. Antibiotics were reported to be the most frequently (41.3%) used self-medication drug for malaria treatment, which is similar to the findings of Kehinde and Ogunnowo.…”
Section: Discussionmentioning
confidence: 76%